Why Does Private Consumption Rise After a Government Spending Shock? - Bouakez, Hafedh; Rebei, Nooman (Bank of Canada, 2003)
Recent empirical evidence suggests that private consumption is crowded-in by government spending. This outcome violates existing macroeconomic theory, according to which the negative wealth effect brought about by a rise in public expenditure should decrease consumption. In this paper, we develop a simple real business cycle model where preferences depend on private and public spending, and households are habit forming. The model is estimated by the minimum-distance and the maximum-likelihood methods using U.S. data. Estimation results indicate a strong Edgeworth complementarity between private and public spending. This feature enables the model to generate a positive response of consumption following a government spending shock. In addition, the impulse-response functions generated by the estimated model mimic closely those obtained from a benchmark vector autoregression.

Des travaux empiriques récents portent à croire que les dépenses publiques ont un effet d'entraînement sur la consommation privée. Ce résultat contredit la théorie macroéconomique, selon laquelle l'effet de richesse négatif engendré par une hausse des dépenses publiques devrait faire baisser la consommation. Les auteurs de la présente étude élaborent un modèle simple de cycles réels dans lequel les préférences dépendent des dépenses privées et publiques, et où les ménages forment des habitudes. Le modèle est estimé à partir de données américaines au moyen des méthodes du minimum de distance et du maximum de vraisemblance. Les résultats des estimations indiquent une forte complémentarité au sens d'Edgeworth entre les dépenses privées et publiques. Grâce à cette propriété, le modèle est capable de générer une réaction positive de la consommation après une augmentation des dépenses publiques. Par ailleurs, les courbes de réaction générées par le modèle estimé imitent remarquablement bien celles obtenues à l'aide d'une autorégression vectorielle.